PERILAKU HIDUP SEHAT DUSUN KLITIH, DRIYOREJO TANGGAP DAN SADAR COVID-19 - Wardhani, Tira Fitria; Prasetyo, Liandi (Jurnal ABDI Bhayangkara, 2022)
Klitih Hamlet is one of the hamlets in Radegansari Village, Driyorejo, Gresik Regency. Klitih Hamlet itself has a good social life and still uses traditional and modern methods, such as when the neighbors have events or celebrations for all their neighbors to work together to help, the people in this hamlet are still fairly genuine or few newcomers in this hamlet, and in this hamlet. rich or poor, there is almost no difference. It’s just that the people are less aware of the regulations and appeals in the Covid-19 pandemic situation. At present in Klitih hamlet (especially in the area of RT 03 Klitih hamlet) the people still do not believe whether the virus really exists. In this hamlet, almost all of the people do not apply social distancing and no one wears a mask, now we are doing a socialization about the dangers of the covid-19 virus, how do people cut off the spread of the virus, and the importance of wearing masks, keep your distance from each other and Maintain cleanliness from starting to wash hands every time you do activities and use a hands-on freezer. Because here we see that the people really ignore all the advice from the government, now we are here to take an approach we socialize by entering into community chats around the Klitih hamlet Rt 03.